Future Perfect?: Teachers' Expectations and Explanations of their Latino Immigrant Students' Postsecondary Futures. Issue 1 (2nd January 2018) - Dabach, Dafney Blanca; Suárez-Orozco, Carola; Hernandez, Sera J.; Brooks, Maneka Deanna
ABSTRACT: Teacher expectancy research has demonstrated the greatest effects for members of racialized groups. Most research has focused on students' near-term abilities; missing are understandings of how teachers perceive their students' future trajectories. Drawing on social mirroring and attribution theories, this study investigates how 14 elementary, middle, and high school teachers of Latino immigrant students described and explained their students' post-high school futures. Most teachers described their students as non-college-bound, with employment likely in the service sector. They attributed their students' futures to family related explanations more often than to structural factors. The study's implications emphasize the need to develop deeper understanding of structural inequalities that mediate students' trajectories including schooling factors.